Assessment of the spaces between the developed and undeveloped areas in Rongo town - Auma, Timon Oluoch; Ang’awa, Francis; Tonui, Warkach K. (International Journal of Humanities and Social Science Intervention, 2016)
The establishment of any urban centres is always characterised by either commercial, industrial or administrative activities. Rongo Town is one of the towns that has attracted a large population and this has led to inadequate houses for the residents and general stress in the provision of social amenities. The general objective of the study was to analyse the socio-economic impacts of Rongo urban sprawl. The specific objective of the study was to assess the spaces between the developed and undeveloped area of Rongo Town. This was important because it projected the causes of inadequate housing units in Rongo Town. Concentric Urban Theory was used to guide the study. Cross sectional design method was used in the study. Quantitative and qualitative design methods were used to give the study a structure. The target population was 27,759. From this 6,095 households were used as respondents. Primary and secondary data were collected. Primary data was collected by use of questionnaires, observation checklist, photographs and sketches. Secondary data involved written articles by experts in urban growth and information in government offices and non-governmental organisations. This data was analysed by Statistical Package for Social Sciences which yielded descriptive and inferential statistics. This data was also analysed by content analysis through description. The spaces between the developed and undeveloped areas were found to be so large. The study recommended the construction of high density houses by filling in the spaces between the developed and undeveloped areas in Rongo Town with houses and other necessary infrastructures.
Keywords: Compact; expansion; infilling; infrastructure; outlying; planning; urban design